2017
DOI: 10.1080/13218719.2017.1396863
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives of Inpatient Forensic Psychiatric Rehabilitation in a Low Secure Setting: A Qualitative Study

Abstract: There is a dearth of research into what low secure forensic psychiatric rehabilitation means in Australia and internationally. The aim of this study was to understand clinician perspectives of forensic psychiatric rehabilitation in a low secure setting in Australia and offer insight into a model of care. A qualitative methodology was chosen with separate semi-structured interviews being conducted with staff members involved in decision-making for forensic psychiatric patients in a rehabilitation unit. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is possible that the Assuring Transformation Data (NHS England, n.d.) may provide similar answers relative to rehabilitation. Furthermore, recent research suggested that clinicians had a thorough understanding of the characteristics of rehabilitation services, which patients are suitable, and the treatment and support goals in a forensic rehabilitation service in Australia (Khan et al, 2017). The authors conducted semi-structured interviews, highlighting that staff emphasized higher degrees of relational and procedural security, and lower degrees of physical security, emphasis on skill development and increasing independence, and working to support patients to understand the clinical and social factors which may lead to reoffending, through supervised and unsupervised access to the community, where patients have access to potential destabilizers, such as drugs and alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the Assuring Transformation Data (NHS England, n.d.) may provide similar answers relative to rehabilitation. Furthermore, recent research suggested that clinicians had a thorough understanding of the characteristics of rehabilitation services, which patients are suitable, and the treatment and support goals in a forensic rehabilitation service in Australia (Khan et al, 2017). The authors conducted semi-structured interviews, highlighting that staff emphasized higher degrees of relational and procedural security, and lower degrees of physical security, emphasis on skill development and increasing independence, and working to support patients to understand the clinical and social factors which may lead to reoffending, through supervised and unsupervised access to the community, where patients have access to potential destabilizers, such as drugs and alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conducted semi-structured interviews, highlighting that staff emphasized higher degrees of relational and procedural security, and lower degrees of physical security, emphasis on skill development and increasing independence, and working to support patients to understand the clinical and social factors which may lead to reoffending, through supervised and unsupervised access to the community, where patients have access to potential destabilizers, such as drugs and alcohol. Staff also discussed the need for support at this critical time in a patient’s care pathway, ‘it is a stepping stone for forensic patients to re-engage in community living’ (Khan et al, 2017: 5).…”
Section: Discussionmentioning
confidence: 99%